2022
DOI: 10.1021/acs.orglett.2c03247
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Three-Component Carboarylation of Unactivated Alkenes with Protic C(sp3)–H Feedstocks

Abstract: A general and mild strategy involving threecomponent carboarylation of unactivated alkenes with protic C(sp 3 )−H feedstocks via photoredox catalysis was reported. This catalytic system is compatible with a broad range of unactivated alkenes, cyano-substituted arenes, and diverse protic C(sp 3 )−H feedstocks. The synthetic value of this protocol was demonstrated by the late-stage functionalization of complex molecules and the synthesis of the antiallergies including pheniramine, chlorpheniramine, and brompheni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Based on these experimental results and related literature, 7–13,16 a proposed mechanism is shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Based on these experimental results and related literature, 7–13,16 a proposed mechanism is shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 88%
“…To further demonstrate the potential synthetic application of our method, a gram-scale reaction was carried out to afford 4k in 72% yield (Scheme 4A). We also employed styrenes derived from bioactive natural products and drugs, including estrone ( 7), L-proline (8), L-menthol (9), oxaprozin (10), ibuprofen (11), probenecid (12), and flurbiprofen (13). We found that the reaction could successfully furnish the corresponding products in good yields (Scheme 4B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For similar alkene difunctionalization reactions, [101] photo-induced multicomponent bifunctionalization of unactivated alkenes were also developed through decyanative strategy by the Lin group [102] and Deng group, [103] respectively (Scheme 29). In Lin's work, arylsilylation of alkenes under a transition-metal free with visible-light irradiation was realized by photoredox and HAT catalysis, this methodology offered a rapid strategy to silicon-containing complex compounds with wide substrate scope and good functional group tolerance.…”
Section: Photo-redox Catalyzed Radical Decyanative Arylation Enabled ...mentioning
confidence: 99%
“…Continuing our interest in visible-light-induced alkylation reactions, herein, we report a mild protocol of visible-light-induced bromoallylation and alkylation of BCBs in a metal- and additive-free manner. The 2-isopropylthioxanthone catalyst plays different roles in this photoinduced divergent functionalization of BCBs.…”
mentioning
confidence: 99%